A Survey of Traceback Based on Probabilistic Packet Marking Under DDoS Attacks. Issue 5 (June 2019) - Zhou, Linna; Jiang, Hui; Zhou, Xinli
Abstract: DDoS attacks are mostly adopted by attackers in the network. This attack is malicious on the network protocol, resulting in the object not working properly. At present, the Packet Marking is the main method to trace back the attackers under DDoS attacks, especially the Probabilistic Packet Marking (PPM) of Packet Marking. Therefore, the two main types of Probabilistic Packet Marking are studied in this paper: Advanced Packet Marking and Authenticated Packet Marking (APM) and Adjusted Probabilistic Packet Marking (APPM).